Behavioural changes in patients with intellectual disability treated with brivaracetam - Andres, Elisa; Kerling, Frank; Hamer, Hajo; Winterholler, Martin (Acta Neurologica Scandinavica, 2018)
OBJECTIVE: The purpose of this study was to evaluate the tolerability and efficacy of brivaracetam (BRV) in residential patients at our epilepsy centre. PATIENTS AND METHODS: We assessed retrospectively 33 patients (14 females; mean age 38.2 years, with range 17-63 years) with intellectual disability (ID) and drug-resistant epilepsy using an industry-independent, non-interventional study design based on standardized daily seizure records. Mean seizure frequency was compared between the 3-month baseline period and subsequent 3-month treatment period. Evaluation, including calculation of retention rate, was carried out for the intervals 3-6 and 9-12 months after brivaracetam initiation. Responders were defined as having a 50% reduction in seizure frequency. The Clinical Global Impression scale (CGI) was applied to allow assessment of qualitative changes in seizure severity, and the Aggressive Behaviour Scale (ABS) gave further insights into challenging behaviour. RESULTS: The responder rate was 19%, and one non-responder attained an improvement in CGI score. The retention rate after 12 months was 37%. Brivaracetam treatment was stopped because of adverse events (n = 3), lack of efficacy (n = 8) or both (n = 6). Thirteen patients experienced behavioural changes, with aggressive behaviour being the commonest effect. We also observed ataxia (n = 2), gastrointestinal disorder (n = 3) and sedation (n = 2). The ABS showed deterioration, or new occurrence, of aggressive behaviour in 13 patients. CONCLUSIONS: Brivaracetam seems to be effective in a small number of patients suffering from difficult-to-treat epilepsy and intellectual disability. Challenging behaviour was documented in a relevant number of patients, with psychiatric illness being a risk factor for this.
EVALuna2:36386